Feelings in Travel Episodes and Extreme Temperatures - Ignacio Belloc; José Ignacio Gimenez-Nadal; José Alberto Molina (Institute of Labor Economics (IZA), 2023)
In recent decades, global warming and its relationship to individual well-being has concerned researchers and policy makers, with research focusing on the consequences of global warming on well-being. In this paper, we analyse the relationship between weather conditions and the feelings reported by individuals during daily travel episodes. We use data from the Well-Being module of the American Time Use Survey for the years 2010, 2012, 2013, and 2021, together with county-level weather information. Our findings indicate an association between extreme temperatures and certain measures of affective well-being while commuting, and notable differences are found, depending on the main travel purpose. In the current context of global warming, when daily temperatures are expected to rise in the future and heat waves will become more frequent, our findings indicate that certain travel activities could be more sensitive to rising temperatures, from an affective perspective, which may help to complement the well-being consequences of global warming.
Keywords: R40; I10; J22; 330; well-being; travel episode; purpose; extreme temperatures; time use; ATUS